2019
DOI: 10.1111/jog.13887
|View full text |Cite
|
Sign up to set email alerts
|

A case of ovarian teratoma with nephroblastoma presenting spontaneous rupture

Abstract: Nephroblastoma (also known as Wilms’ tumor) mainly occurs in the kidneys of children. Nephroblastoma outside the kidneys may be observed in three situations: primary disease, metastatic disease and nephroblastoma arising in teratoma. Teratoma with nephroblastoma (TWN) of the adult ovary is a rare tumor and only one case has been reported. We report an unusual adult case of ovarian TWN presented to us with acute abdomen due to the spontaneous rupture of the ovary. The rupture occurred at the site of TWN, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Nephroblastoma has been discovered to affect the function of unilateral or bilateral kidneys ( 33 , 34 ). Although the diagnosis and treatment of nephroblastoma has significantly improved, the mortality rate of nephroblastoma in children remains high (10.7%) ( 35 , 36 ). Thus, studying the effects of factors related to early nephroblastoma may provide a novel target and treatment method for nephroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Nephroblastoma has been discovered to affect the function of unilateral or bilateral kidneys ( 33 , 34 ). Although the diagnosis and treatment of nephroblastoma has significantly improved, the mortality rate of nephroblastoma in children remains high (10.7%) ( 35 , 36 ). Thus, studying the effects of factors related to early nephroblastoma may provide a novel target and treatment method for nephroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous similar cases in Table 1, two cases received fertility‐preserving surgery 1,3 . The other case showed intra‐peritoneal dissemination shortly after primary excision of a ruptured tumor, and then complete remission after second complete staging surgery with adjuvant chemotherapy 2 …”
Section: Figurementioning
confidence: 89%
“…To the best of our knowledge, immature renal tissue in ovarian teratoma is extremely rare, with only three cases being reported previously (Table 1). [1][2][3] The pathogenesis of the tumor was unclear, and various nomenclatures have been used to describe this phenomenon: immature renal tissue in teratoma, teratoma with nephroblastoma/Wilms tumor, and teratoid Wilms tumor. Coli et al suggested that immature renal tissue is generally not aggressive and should be differentiated from a true Wilms tumor, based on atypia, atypical mitoses, marked pleomorphism and expanding growth.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the pathogenesis of TWN is still controversial. Some researchers believe that majority of these tumors are pure nephroblastomas, but that only a small part of it originates from teratomas or germ cell neoplasms, 6 while some other investigators favor that TWN is thought to be aroused from extensive metaplasia of metanephric blastema. 7 Moreover, TWN has been presented in various locations.…”
Section: Discussionmentioning
confidence: 99%